IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING EXTENSIVE READING AT SMP MUHAMMADIYAH LUWUK - Abdul Rabbi Arrasul; Nursina Abdul Halim (English Education Study Program, 2021)
The objective this research is to look for the improvement of students’ vocabulary mastery through extensive reading at SMP Muhammadiyah Luwuk. This research used a pre-experimental research design with one group pretest and posttest design. The population of this research was the students of ninth grade students of SMP Muhammadiyah Luwuk consisted of twenty-two students. The sample of this research was all the population of the research. In collecting data, the researcher used test. The test consisted of pretest and posttest. Data were analyzed statistically. After being analyzed, it was found that the result of the t-counted was 12,215. With 21 degree of freedom, and a the significance level of 0,05, the t-table was 1,721.Therefore, the result of t-counted is bigger than t-table. It is clear that the research hypothesis is received. In other words, the implementation of extensive reading can improve students’ vocabulary mastery of the ninth grade students at SMP Muhammadiyah Luwuk.